Private places and collective uses: From consumption new world to new retail typologies in Lisbon (Ciudades, 2018)
Behaviour changes related with leisure, after the second half of the Twentieth Century, intensify and diversify retail activities. Commerce, culture and leisure organize the contemporary urban space. Therefore new retail areas polarize the urban settlements. Consumption has a clear social meaning. Everything can be transformed into consumption. Retail centres are provided with systems of security and control, used like elements of well-being. Comfortable atmospheres are created where nobody is worried, but the desire of re-moducing the traditional public space performs copies of those places, as pieces of reality in artificial scenes.First, retail parks were settled in the Lisbon and Oporto metropolitan zone, but now they are also located in smaller cities. Retail is considered in the regional settlement and used as a tool of city-planning.
Keywords: Privatization of public spaces; consumption; Lisbon